2020
DOI: 10.1002/jmv.26509
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tocilizumab in COVID‐19: A systematic review and meta‐analysis

Abstract: The efficacy of tocilizumab (TOC), monoclonal antibody against interleukin‐6 (IL‐6) receptor, in patients with coronavirus disease‐2019 (COVID‐19) patients has led to conflicting results. We performed a systematic review and meta‐analysis to compare the efficacy of addition of TOC to standard of care (SOC) versus SOC in patients with COVID‐19. We performed a comprehensive literature search of PubMed, Embase, Web of Science, WHO COVID, LitCOVID, and Cochrane databases. Pooled outcomes (overall mortality, need f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 45 publications
2
85
1
6
Order By: Relevance
“…The most recent systematic reviews on the use of TCZ for COVID-19 identified clinical trials without data synthesis (Cortegiani et al, 2020) and performed a large meta-analysis of controlled trials but did not address issues with the individual studies (Aziz et al, 2020). Therefore, this systematic review will synthesize the evidence from individual case-control studies, analyze uncontrolled trials and evaluate their methods to Figure 3 IL-6 pathway and TCZ mechanism of action.…”
Section: Il-6 Inhibitor Tocilizumabmentioning
confidence: 99%
“…The most recent systematic reviews on the use of TCZ for COVID-19 identified clinical trials without data synthesis (Cortegiani et al, 2020) and performed a large meta-analysis of controlled trials but did not address issues with the individual studies (Aziz et al, 2020). Therefore, this systematic review will synthesize the evidence from individual case-control studies, analyze uncontrolled trials and evaluate their methods to Figure 3 IL-6 pathway and TCZ mechanism of action.…”
Section: Il-6 Inhibitor Tocilizumabmentioning
confidence: 99%
“…A previously published meta-analysis showed that COVID-19 patients treated with tocilizumab had reduced mortality, less need for mechanical ventilation, improved respiratory function, rapid defervescence, and successful discharge compared with the control group, especially when the subgroup analysis was restricted to studies that only included patients with severe COVID‐19 based on the clinical picture and laboratory parameters [21] , [22] , [23] . Our study is consistent with these studies, and the samples were restricted to severe COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent systematic reviews on the use of TCZ for COVID-19 identified clinical trials without data synthesis 26 and performed a large meta-analysis of controlled trials but did not address issues with the individual studies. 27 Therefore, this systematic review will synthesize the evidence from individual case-control studies, analyze uncontrolled trials and evaluate their methods to determine whether the drug is potentially effective at reducing severe COVID-19-related mortality, thus corroborating the logic for continuing RCTs to evaluate the potential use of IL-6 inhibitors.…”
Section: Il-6 Inhibitor Tocilizumabmentioning
confidence: 99%